Imaging Identification and Prognosis of the Distal Internal Carotid Artery With Near and Complete Occlusion After Recanalization - Sun, Tao; Wang, Chao; Han, Mengtao; Wang, Fei; He, Yiming; Wang, Yunyan; Li, Xingang; Wang, Donghai (Frontiers in Neurology, 2021)
Abstract Background and Purpose: Previous studies have mainly focused on treatment strategies and clinical outcomes for internal carotid artery near occlusion (ICANO) and internal carotid artery complete occlusion (ICACO). However, reports on the morphological changes of distal internal carotid artery (ICA) after recanalization are scarce. This study aimed at illustrating identifying features, assessing prognosis of the distal ICA after recanalization, and exploring best practices for treatment for ICANO and ICACO. Materials and Methods: We retrospectively studied the clinical characteristics of 57 patients with ICANO or ICACO who underwent surgical recanalization. The clinical data, angiographic morphology, technical successful rate, perioperative complications, and the lumen changes of distal ICA before and after successful recanalization were analyzed. Results: Fifty-two patients who achieved successfully recanalization were studied. Based on the postoperative lumen diameter changes in the distal ICA, 19 cases were classified as distal-dilatation and the remaining 33 as distal-narrowness. Patients in the distal-narrowness group mostly had ICACO (21.1% vs. 54.5%) and were men (68.4% vs. 93.9%). In the distal-narrowness group, the lumen of the distal ICA recovered to normal in 32 of the 33 patients during the follow-up period. Of the 32 patients reviewed, the ICA of 28 patients dilated back to normal after 1 week of surgery; the ICA of remaining patients 4 dilated 2 weeks postoperatively. Conclusions: Narrowness of the distal ICA after hybrid recanalization was more prevalent in male patients with ICACO. Homogeneous stenosis of the whole course of the distal ICA is a low-perfusion narrowness which does not require intervention and will spontaneously recover after successful recanalization with an increase in the forward flow.